2007
DOI: 10.1192/apt.bp.106.003442
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in dementia: issues and evidence

Abstract: Palliative care is an approach that stands well with the aims of person-centred dementia care. There is no doubt that the standards of care for many people with advanced dementia are poor. There is a lack of good-quality evidence, however, to support any particular approach for palliative care in dementia. Still, there are a number of areas in relation to caring for people with severe dementia where a palliative approach might be beneficial. In general, the relevant decisions have to be made on an individual b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
24

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 87 publications
0
55
0
24
Order By: Relevance
“…This review complements the work of others that have demonstrated how fragmented and descriptive research on end-of-life care for people with dementia is regardless of setting, and the absence of work that is dementia specific (Hughes et al, 2007). What this review starkly illustrates however, is the lack of interventions and outcome measures for providing end-of-life care in the settings where the majority of this population live and die.…”
Section: Discussionmentioning
confidence: 67%
“…This review complements the work of others that have demonstrated how fragmented and descriptive research on end-of-life care for people with dementia is regardless of setting, and the absence of work that is dementia specific (Hughes et al, 2007). What this review starkly illustrates however, is the lack of interventions and outcome measures for providing end-of-life care in the settings where the majority of this population live and die.…”
Section: Discussionmentioning
confidence: 67%
“…Evidence exists that the care of people with dementia, especially towards the end of their lives, is less than optimal (195). Palliative care stands well with the aims of person-centred dementia care and is beneficial in relation to caring for people with dementia.…”
Section: Palliative Carementioning
confidence: 99%
“…93 Several reviews point unequivocally to the importance of adopting palliative approaches in the case of non-malignant diseases such as dementia, particularly in acute settings. [94][95][96] There is also continuing evidence of inequalities in referral to and use of specialist palliative care services for older people. 20 Older people are proportionally more likely to die from conditions other than cancer, and hence are disadvantaged in access to specialist palliative care services by diagnosis.…”
Section: Introductionmentioning
confidence: 99%